Medieval Wood Sculpture of an Unknown Saint from Nousiainen: from Materials to Meaning - Vuola, Katri; Reijonen, Henni; Kaasalainen, Touko; Saat, Riste (Mirator, 2018)
This article takes up from an interdisciplinary perspective the issue of placing relics inside wooden sculptures during the Middle Ages in Finland. In the focus of the study is a late thirteenth-century sculpture depicting a standing saint from the memorial church of Saint Henrik in Nousiainen (Nousis), South-Western Finland, now in the collection of the National Museum of Finland. The identity and even the gender of the “Unknown Saint” has puzzled art historians, most recently in the 1960s. On the basis of a new visual and technical examination as well as iconographical and stylistic analysis of the sculpture, alternative interpretations of the identity of the depicted saint as well as of the origin and function of the sculpture are suggested. The current article also includes a detailed description of the dual-energy and ultrahigh-resolution CT-scanning of the sculpture at the HUS Medical Imaging Center at the Helsinki University Hospital. This is the first time that CT-scanning has been used to research medieval wooden sculpture in Finland. Discoveries made during the inspection were interpreted as possible relics. Consequently, the function of the sculpture is further discussed in the context of the cult of relics in Finland.